The political economy of cultural heritage conservation and tourism development of the City of Manila - Cruz, Geoffrey Rhoel C. (Animo Repository, 2022)
Over the years, cities across the world have experienced unprecedented growth and development imposing greater demands to states and cities alike, resulting in the unsustainable use of finite resources. Such growth has been associated with high levels of environmental damage and social dislocation; hence affecting cities’ competitiveness, efficiency and livability, and overall sustainability. The City of Manila, Philippines, is not an exemption. In the 2018 Sustainable Cities Index published by Arcadis Design and Consultancy, the City of Manila was ranked 95thoverall out of 100 countries surveyed, one notch better than its 2016 performance. The City of Manila was indexed at 93rdfor people (94thin 2016), 91stfor planet (86thin 2016), and 98th (91stin 2016) under the profit category. As developing countries follow the linear pattern of development, modernization has likewise contributed to the development of urban decay thus compromising cultural heritage. As such, this study addresses the central question of “How does the current tension between cultural heritage conservation and tourism development objectives impact the sustainability of the City of Manila?”. In answering the research question, the study utilizes the economic framework developed by Russo and Van der Borg (2006) called Culture-Oriented Economic Development (COED) that was locally adapted as the heritage-driven development by Zerrudo (2020) which focuses on culture as the fourth pillar of sustainability. The framework, while considering the contrasting perspectives and interests of the different shareholders, provides that culture, as empowered through cultural heritage conservation with tourism as an approach, contributes to the sustainability of the City of Manila. A heritage-driven development will yield 1) sustainable inclusive and equitable outcomes; 2) acknowledge and promote respect for cultural diversity in preventing conflict and protecting the rights of marginalized groups; 3) capitalize on the culture sector’s contribution to economic development and poverty reduction. This qualitative study adopts the method of semi-structured online key informant interviews in view of the pandemic. Furthermore, stakeholders analysis was used to assess and understand the actors involved in cultural heritage conservation and tourism development in the City of Manila. This study examined whether the conflict between cultural heritage conservation and tourism development affects the sustainability of the City of Manila. Various stakeholders and their level of participation in the conceptualization and implementation of the tourism development plan of Manila were also identified. Its implications to the city’s sustainability based on the sub-index of People and Profit under the Arcadis Sustainable Cities Index were likewise assessed. The findings of this study confirm that a conflict exists between the stakeholders involved in heritage conservation and tourism development of the City of Manila. As different interests clash, the sustainability of the City of Manila is greatly compromised. The mandate of promoting the overall development of tourism has been the cornerstone of the national government’s policies, while the local government extends the concern to include developing the urban landscape and at the same time address other development concerns like poverty, job creation, and zoning policies. Moreover, the cluster of the NGOs, CBOs, and heritage advocates focuses on the preservation of urban identity, the sense of place, and pride that comes with historical preservation; while the group of private organizations and business groups focus on the maximization of economic interest and business profit. In the end, cultural heritage takes the backseat as minimal attention has been given to its conservation. The tension between heritage and development stems from the lack of awareness on the part of the stakeholders. To most, cultural heritage, tangible or intangible, is just an ordinary concept that nostalgic people still adhere to.Others see heritage as a hindrance to development as the old dichotomy of heritage and development provides such that the usual practice is for cultural heritage to give way to the principles of development leading to the destruction of built cultural heritage. As this study affirms, cultural heritage refers to the promotion of every sense of life colloquially. The success stories of heritage-drive development in other countries have laid down the cornerstone for culture to serve as the fourth pillar of sustainable development goals. Thus, the community must understand the relevance of heritage to their lives and learn how to find economic value to it. Instead, heritage appreciation and preservation should be done for identity recognition side-by-side with its corresponding tangible and intangible benefits. However, there is a lack of local studies that can debunk the view that cultural heritage cannot contribute to economic development. In conclusion, the various success stories of a heritage-driven economy or a cultural-oriented economic development across literature have proven that cultural heritage can generate a circular economy, thus spelling out the narrative of heritage versus modernity as a modern myth or urban legend. Indeed, heritage can work side-by-side with development.With culture and heritage serving as a core part of the economy’s backbone through an effective development intervention of a sustainable urban revitalization, it can promote a creative economy by generating employment opportunities and improving existing economic conditions resulting in direct and indirect economic benefits, in addition to non-monetized benefits like the personal-psychological reward of being proud to preserve the heritage and contribute towards ensuring future generations of a heritage to remember. Looking at the strengths and opportunities of the innate character of the City of Manila having a very rich history and culture, without a doubt, heritage is one of its greatest assets. Thus, this study’s theoretical contribution to the field of cultural heritage conservation is a “Heritage-Driven Urban Revitalization Framework” that can be considered for the revitalization of the historic urban landscape of the City of Manila. In a sustainable urban revitalization intervention, short-term strategies and long-term strategies are pursued aiming to offer a holistic improvement of the three facets of sustainable development. The short-term strategies focus on the physical revitalization of the urban fabric thus, covering the environmental factors categorized under the Planet sub-index of the Arcadis Sustainable Cities Index referring to efficient management of energy use, pollution, and emission. While long-term strategies are aimed at economic revitalization and social revitalization covering the Profit sub-index, referring to economic performance and business infrastructure; and the People sub-index measuring social mobility and quality of opportunity in life. Therefore, a sustainable urban revitalization intervention has the power to breed physical, economic, and social sustainability for the City of Manila.